Blue-green urban oasis: creating strategic cool spots in overheated neighbourhoods - Mariana Pereira Guimaraes; Valentina Dessì (Techne)
The paper presents a methodology for adapting to urban overheating by creating strategically located blue-green oases – combining vegetation and water systems to enhance neighbbourhood thermal comfort. Focusing on Milan’s Corvetto district as an example, the methodology includes 1) identifying socio-environmentally vulnerable neighbourhoods at the city scale; 2) mapping existing cool spots within the neighbourhood; 3) identifying areas beyond a 5-minute walking radius from these cool spots; and 4) proposing local interventions, such as water-based solutions (WBS), in urban spaces that could become new “cool spots”. The results highlight a network of potential new cooling spaces.